Children of Parents With Serious Mental Illness: The Perspective of Social Workers. Issue 4 (8th August 2017) - Afzelius, Maria; Plantin, Lars; Östman, Margareta
Abstract : The aim of this study is to describe the experiences of children's social workers in Sweden who work with families in which a parent suffers from serious mental illness, and how a child in such a family receives support. Data were collected through individual interviews and focus groups discussions with 13 professionals in 2 minor municipalities in southern Sweden. Interviewees stated that parental serious mental illness was not a main focus for children's social workers. When parental serious mental illness became a barrier to caring for their children, the children's social workers sought to collaborate with psychiatric services, but in many cases it did not turn out well. Providing support to the parent was one way of aiding the family, although at the price of setting the child's perspective aside. Being faced with responsibility for the parent and the child left children's social workers feeling they were the last outpost for the families. Children's social workers require greater knowledge of how to handle parental serious mental illness, and more interagency collaboration with psychiatric services is needed to adequately support children of parents with a serious mental illness.